A organização de preferência em cartas de pedido de empresas estatais brasileiras - Oliveira, Maria do Carmo Leite de (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The present study applies the notion of preference organization to letters of request from two Brazilian state-owned companies. The aim is to critically examine this notion in written texts, as applied to the first part of an adjacent pair. We argue, in the light of Brown & Levinson's (1987-[1978]) politeness theory, that request may be classified according to different degrees of preference which reflects the need or intention to negaciate the control of relationship